Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11648/j.ajns.20170605.17
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s Level of Knowledge on Neonatal Danger Signs and Its Predictors in Chencha District, Southern Ethiopia

Abstract: Abstract:Introduction: Neonates and young infants often present with non-specific symptoms and signs of severe illness that indicate presence of severe infection which may require immediate care. So, mother's knowledge is very important to recognize those symptoms to prevent further complications even dealth. But there is a gap in assessing mothers knowledge in neonatal danger signs. Because, almost all studies in Ethiopia assessed mother's knowledge based on only one danger sign out of nine WHO recognized dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 8 publications
(16 reference statements)
3
32
4
Order By: Relevance
“…The overall mother knowledge of neonatal danger sign this study, is lower than the study conduct in Egipt and Ghana were (68-70%), 71.9% respectively [23,27]. but this result was in line with the study conducted in Bangladesh, Mekele Ethiopia and Chincha district southern Ethiopia which showed mothers knowledge neonatal danger sign of 51, 50.6 and 50.3% respectively [17,20,25][ However, this finding is higher than the study conducted in Nigeria (30.3), Uganda (poor), Kenya (15), Gonder Northwest Ethiopia (18.2), For region of Ethiopia was (29.3), Gedio zone (32.4), Welkite(31.3%) [15,19,26,28]. The possible reason for the observed difference might be due to the extensive work of HEWs in the community and different health care institutions in awareness creation on neonatal danger signs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The overall mother knowledge of neonatal danger sign this study, is lower than the study conduct in Egipt and Ghana were (68-70%), 71.9% respectively [23,27]. but this result was in line with the study conducted in Bangladesh, Mekele Ethiopia and Chincha district southern Ethiopia which showed mothers knowledge neonatal danger sign of 51, 50.6 and 50.3% respectively [17,20,25][ However, this finding is higher than the study conducted in Nigeria (30.3), Uganda (poor), Kenya (15), Gonder Northwest Ethiopia (18.2), For region of Ethiopia was (29.3), Gedio zone (32.4), Welkite(31.3%) [15,19,26,28]. The possible reason for the observed difference might be due to the extensive work of HEWs in the community and different health care institutions in awareness creation on neonatal danger signs.…”
Section: Discussionsupporting
confidence: 81%
“…For health institution delivered mothers, urban women were 3 times more likely to know neonatal danger signs when compared to rural mothers. In agreement with this, studies revealed that the mother's residence determines their level of knowledge of neonatal danger signs [17,29]. For example, the study conducted in Chincha towards mother knowledge neonatal danger sign with residence showed that mothers who lived in urban were two times more likely known as compared to mothers who lived in a rural area.…”
Section: Discussionmentioning
confidence: 78%
“…We followed the methods of Mersha 23 and to ensure quality of data, the questionnaire and checklists were initially drafted in English, and then translated into a local language, "Amharic" by verified translators. Lastly, before data collection, the questionnaire was back translated into English to ensure accuracy.…”
Section: Data Quality Controlmentioning
confidence: 99%
“…All variables with P<0.25 in the bivariate analysis were included in the final model of multivariate analysis in order to control all possible confounders. We followed the methods of Mersha 23 that variables which were significant in previous studies and from context point of view were included in the final model even if the above criteria were not meet. Collinearity statistics was carried out to determine the correlation between the independent variables.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…The postnatal mothers level of knowledge (47.8%) was lower than from Community based cross sectional study conducted in Chencha District, Southern Ethiopia where 50.3% of mothers had good level of knowledge who knows three or more neonatal danger signs. This might be due to the research study design difference [12].…”
Section: Table3 Associations Of the Postnatal Mothers With Differentmentioning
confidence: 99%